Analysis of Language Extinction in Transmigration Communities in Jorong Lubuk Macang Kabupaten Dharmasraya: Analisis Kepunahan Bahasa Pada Masyarakat Transmigrasi di Jorong Lubuk Macang Kabupaten Dharmasraya - faradilla intan sari (Perkumpulan Doktor Indonesia Maju (PDIM), 2020)
Transmigration is a program created by the Indonesia government to move resident from a densely populated area to other regions in Indonesia. Researchers conducted research in Jorong Lubuk Macang because the native language of the transmigration community experienced extinction both orally and in writing. The method used in this research is a qualitative descriptive study. The purpose of this study is to describe the fate of native languages in transmigration communities in Jorong Lubuk Macang, describe the factors that cause the extinction of Javanese languages in Jorong Lubuk Macang, and describe the effots made to maintain the existence of Javanese in globalization era. Researchers took a sample, especially in the Alm Bagiam Familly who are transmigration communities from central Java to Dharmasraya (Jorong Lubuk Macang). The result of reseach on the extinction of language in transmigration communities are the extinction of Javanese that is influenced by the new environment and the results of this study also show the occurrence of nomial language extinction (through metamorphosis of the decline in the level of language) caused by the reduced use of native languages in transmigration communities. Keywords: analysis of language extinction,